SEA SURFACE TEMPERATURE RELATED TO THE BIG EYE TUNA EXISTANCE IN INDIAN OCEAN ON 2010 - MARTIWI DIAH SETIAWATI; FUSANORI MIURA; Tasuku Tanaka (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science), 2012)
Indian Ocean, particularly on Southern part of ,Java and Bali was identified for some big pelagic fish. Among all of the big pelagic fishes, big eye tuna is the highest commercial value compare with other species There are several research which studied the relationship between the existence of tuna and environmental factor. Sea Smface Temperature (SST) was used as a main oceanographic factor to relate with big eye tuna abundance. SST data \\aS derived from Level 3 AQUA M0DIS data. In my paper, 1 use additional simple statistical method to prove that SST and big eye tuna has a good con-elation. I used polynomial regression and geographic information system method to improve correlation value of lhe data. There arc three critical value and four equation. Based on the data analysis, SST has significant value to big eye tuna abundance in Indian Ocean and has high correlation.